A sufficientarian perspective on human development goals - Peeters, Wouter (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
Each account of justice should substantiate the pattern of distribution; the principle according to which distribution should take place. Examples include strict equality, a Rawlsian difference principle, sufficiency, priority, or a combination of some principles. The role of such principle is essentially to determine when justice obtains, and to guide policy decisions in a society aimed at achieving distributive justice for all of its members. In this context, it also forms the tacit foundation of human development goals.
Páginas 127-147
Keywords: Desarrollo humano; Justicia social; https://purl.org/pe-repo/ocde/ford#5.00.00